Utilization and associated factors of traditional bone setting service among patients with musculoskeletal injuries in Northeast Ethiopia - Seid, Mengesha Alemu; Walelgn, Betelhem; Kibret Sendekie, Ashenafi; Walle, Getachew Tesfaw; Geremew, Melkamu Adamu; Sahlu, Mikiyas Haylu; Mekonen, Simachew Asress; Abate, Biruk Beletew (Frontiers in Rehabilitation Sciences, 2025)
BackgroundTraditional bone setting is widely practiced in Ethiopia, despite the lack of standardized training and associated risks. This study aimed to assess the prevalence of traditional bone setting service utilization and associated factors among trauma patients at Woldia Comprehensive Specialized Hospital.MethodsAn institution-based cross-sectional study was conducted between April 9 and May 18, 2024. A total of 420 participants were selected using a consecutive sampling technique. Binary and multiple logistic regressions were used to assess the association between the independent variables and traditional bone setting service utilization.ResultsA total of 420 patients with orthopedic injuries participated in the study. The prevalence of traditional bone setting utilization was 55.2% (95% CI: 50.44, 59.95). In a multivariable regression model, rural residency (AOR = 1.56, 95% CI: 1.02, 2.39), low annual income (<21,000 Birr) (AOR = 4.06, 95% CI: 1.97, 8.37), use of health insurance (AOR = 0.63, 95% CI: 0.41, 0.95), and extremity trauma (AOR = 1.82, 95% CI: 1.11, 2.99) were significantly associated with traditional bone setting utilization.ConclusionTraditional bone setting utilization is common among rural, poor, and uninsured patients. Further research may be important to ensure its appropriate utilization.